Legal Sociology in Costa Rica: Notes for a balance - Ramírez Granados, Mario A. (2022)
This article analyzes the Sociology of Law and it’s differences with the traditionalanalysis. It also identifies it’s principal topics of investigation and some costaricanstudies on Sociology of Law. Finally it proposes the creation of new investigationthemes in this academic area.